Heterogeneous Firms or Heterogeneous Workers? Implications for Exporter Premiums and the Gains from Trade - Irarrazabal, Alfonso; Moxnes, Andreas; Ulltveit-Moe, Karen Helene (The Review of Economics and Statistics, 2013)
We investigate to what extent worker heterogeneity explains the well-known wage and productivity exporter premiums, employing a matched employer-employee data set for Norwegian manufacturing. The wage premium falls by roughly 50% after controlling for observed and unobserved worker characteristics, while the total factor productivity premium falls by 25% to 40%, suggesting that sorting explains up to half of these premiums. Recent trade models emphasize the role of within-industry reallocation of labor in response to various shocks to the economy. Our findings suggest that aggregate productivity gains due to reallocation may be overstated if not controlling for sorting between firms and workers.